Does equity in ways of showing love matter for marital satisfaction? - Huić, Aleksandra (Array, 2012)
The aim of this study was to test the predictions derived from the equity theory, social exchange principle and research dealing with marital climate about the relationship between equity in the ways of showing love between partners and marital satisfaction. The sample consisted of 302 Croatian married couples of different age (20-82 years) and from various urban/rural backgrounds. Marriage length varied between one month and 57 years. Along with asking about marital satisfaction, we administered The Ways of Showing Love Scale. Equity was assessed as a similarity between how much (in total and in every of the six specific ways) an individual shows love to his/her partner and his/her perception of how his/her partner shows love to him/her. According to equity theory, individuals who show and perceive a similar amount of love, no matter whether this amount is big or small, should be more satisfied with their relationship. Individuals who are underbenefited should be less satisfied, while individuals who are overbenefited should be somewhere in the middle. Results did not confirm this hypothesis. We found that both men and women with a high score on both showing and perceiving love are most satisfied with their marriage. Underbenefited and overbenefited individuals do not differ, and have somewhat lesser scores on marital satisfaction. Those with a low score on both showing and perceiving love are the least satisfied. The results suggest the importance of positive socio-emotional climate for marital satisfaction.